Adaptive genetic traits in pelagic freshwater microbes - Chiriac, Maria-Cecilia; Haber, Markus; Salcher, Michaela M (Environmental microbiology, 2023)
Pelagic microbes have adopted distinct strategies to inhabit the pelagial of lakes and oceans and can be broadly categorized in two groups: free-living, specialized oligotrophs and patch-associated generalists or copiotrophs. In this review, we aim to identify genomic traits that enable pelagic freshwater microbes to thrive in their habitat. To do so, we discuss the main genetic differences of pelagic marine and freshwater microbes that are both dominated by specialized oligotrophs and the difference to freshwater sediment microbes, where copiotrophs are more prevalent. We phylogenomically analysed a collection of >7700 metagenome-assembled genomes, classified habitat preferences on different taxonomic levels, and compared the metabolic traits of pelagic freshwater, marine, and freshwater sediment microbes. Metabolic differences are mainly associated with transport functions, environmental information processing, components of the electron transport chain, osmoregulation and the isoelectric point of proteins. Several lineages with known habitat transitions (Nitrososphaeria, SAR11, Methylophilaceae, Synechococcales, Flavobacteriaceae, Planctomycetota) and the underlying mechanisms in this process are discussed in this review. Additionally, the distribution, ecology and genomic make-up of the most abundant freshwater prokaryotes are described in details in separate chapters for Actinobacteriota, Bacteroidota, Burkholderiales, Verrucomicrobiota, Chloroflexota, and 'Ca. Patescibacteria'.
Keywords: jezera; genomika; Bacteria; ekologie; Genomics; Phylogeny; Lakes; fylogeneze; Ecology; ekosystém; Ecosystem